The Anatomy of Behavioral Responses to Social Assistance When Informal Employment Is High - Marcelo Bergolo; Guillermo Cruces (Institute for the Study of Labor (IZA), 2016)
The disincentive effects of social assistance programs on registered employment are a first order policy concern in developing countries. Means tests determine eligibility with respect to some income threshold, and governments can only verify earnings from registered employment. The loss of benefit at some level of formal earnings is an implicit tax that results in a strong disincentive for formal employment. We study an income-tested program in Uruguay and extend previous literature by developing an anatomy of the behavioral responses to this program. Our identification strategy is based on a sharp discontinuity in the program's eligibility rule and uses information from the program's records, social security administration data, and a follow-up survey. First, we establish that beneficiaries respond to the program's incentives by reducing their levels of registered employment by about 8 percentage points. Second, we find the program induces a larger reduction of formal employment for individuals with a medium probability to be a registered employee, suggesting some form of segmentation – those with a low propensity to work formally do not respond to the financial incentives of the program. Third, we find evidence that the fall in registered employment is due to a larger extent to an increase in unregistered employment, and to a lesser extent to a shift towards non-employment. Fourth, we find an elasticity of participation in registered employment of about 1.7, implying a deadweight loss from the behavioral responses to the program of about 3.2% of total registered labor income.
Keywords: H31; I38; J22; O17; 330; welfare policy; labor supply; registered employment; labor informality